Bone mineral density in professional female volleyball players and dietary factors - Huk-Wieliczuk, E. (Theory and Practice of Physical Culture, 2021)
An excessive volume and intensity of physical effort which takes place during sports training, and many years of playing career are not protected against the development of osteoporosis.